Arbuscular Mycorrhiza Enhances Biomass Production and Salt Tolerance of Sweet Sorghum - Wang, Fayuan (Microorganisms, 2019)
Arbuscular mycorrhizal (AM) fungi (AMF) are widely known to form a symbiosis with most higher plants and enhance plant adaptation to a series of environmental stresses. Sweet sorghum (Sorghum bicolor (L.) Moench) is considered a promising alternative feedstock for bioalcohol production because of its sugar-rich stalk and high biomass. However, little is known of AMF benefit for biomass production and salt tolerance of sweet sorghum. Here, we investigated the effects of Acaulospora mellea ZZ on growth and salt tolerance in two sweet sorghum cultivars (Liaotian5 and Yajin2) under different NaCl addition levels (0, 0.5, 1, 2, and 3 g NaCl/kg soil). Results showed AMF colonized the two cultivars well under all NaCl addition levels. NaCl addition increased mycorrhizal colonization rates in Yajin2, but the effects on Liaotian5 ranged from stimulatory at 0.5 and 1 g/kg to insignificant at 2 g/kg, and even inhibitory at 3 g/kg. High NaCl addition levels produced negative effects on both AM and non-AM plants, leading to lower biomass production, poorer mineral nutrition (N, P, K), higher Na(+) uptake, and lower soluble sugar content in leaves. Compared with non-AM plants, AM plants of both cultivars had improved plant biomass and mineral uptake, as well as higher K(+)/Na(+) ratio, but only Yajin2 plants had a low shoot/root Na ratio. AM inoculation increased the activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), and soluble sugar content in leaves. Overall, both cultivars benefited from mycorrhization, and Yajin2 with less salt tolerance showed higher mycorrhizal response. In conclusion, AMF could help to alleviate the negative effects caused by salinity, and thus showed potential in biomass production of sweet sorghum in saline soil.